Komunikacijska priprema trenera ili zašto i kako "trenirati" komunikacijske vještine? - Bartoluci, Sunčica; Tomić, Diana (2010)
Communication skills still do not receive enough attention in the field of physical conditioning, regardless of the growing number of references dealing with communication phenomenon arising from other disciplines i.e. psychology, sociology, pedagogy, phonetics, linguistics, economic science. It is well known that the survival of humans as social beings depends on their ability to interact with their surroundings. It is assumed that since humans develop language during the socialization process we develop communication skills as well. However, communication development can not be implied since the success in the process largely depends on the effort invested in it. It is the hard and methodical work that produces a great coach and not pure luck. For a coach to effectively transfer both theoretical and practical knowledge it is necessary to develop and train communication skills.
Projekt MZOS
Projekt MZOS
HRV